Genetic Structure in Long Tailed Macaque Populations in The Region of East Java: Diversity of Mithochondrial DNA in Alas Purwo and Baluran Population - I Nengah Wandia; I Gusti Agung Arta Putra; I Gede Soma (Veterinary Science and Medicine Journal, 2015)
Long tailed macaque (Macaca fascicularis) has distributed throughout the regions in Indonesia, however,they, now, live separately to many local populations within an island. This research aimed to explore thegenetic diversity within and between populations of long tailed macaque in the Region of East Java. Thegenetic diversity was examined by molecular marker of d-loop region mtDNA using a pair of specificprimers. A total of 29 blood samples (15 samples from Alas Purwo population and 14 samples fromBaluran population) was extracted to find out a total DNA. The d-loop region mtDNA was amplifiedthrough PCR tecnique. The PCR products were sequenced using dideoxynucleotide chain terminationmethod at Macogen Inc. Korea. The research found 6 haplotypes, in which 3 haplotypes were found in eachpopulation. Haplotype and nucleotide diversities varied from 0.257 to 0.275 and 0.0012 to 0.0025repectively. Genetic differentiation between populatioon was F=44.1%. Phylogenetic reconstructionshowed that all haplotypes constructed  two different groups (haplogroups)  and there was no sharedhaplotype betwen populations. It can be concluded that both populations (Alas Purwo and Baluran) areuique and have low genetic diversities.